AI for sustainable business : leveraging technology for a better future - Rezaee, Zabihollah, 1953-; Boumediene, Salem L.; Homayoun, Saeid; Boumediene, Salma (Routledge, 2026)
This essential guide empowers readers to leverage artificial intelligence (AI) as a tool for efficiency, financial viability, growth and innovation, and as a force for positive social and environmental impact, creating sustainable shared value for all stakeholders. It explores the transformative role of AI in advancing business sustainability and explains how technology and the use of AI, including generative AI (GenAI) and large language models (LLMs), can foster and promote sustainability initiatives as well as measure, report, and analyze key performance indicators in sustainability.AI for Sustainable Business offers a strategic roadmap for integrating AI to foster responsible, long-term sustainable business practices. Using straightforward language, the book helps unpack the sometimes complex theoretical and practical concepts and procedures. As businesses increasingly recognize the importance of sustainability, the challenge lies in effectively integrating sustainable practices with advanced technologies. The book addresses this challenge by offering practical insights, frameworks, and case studies that illustrate the successful implementation of AI in various business contexts. It highlights the potential of AI to optimize resource use, reduce environmental impact, and improve corporate governance while maintaining a competitive advantage. This book enables businesses to make more informed decisions, optimize their operations, and promote sustainable practices, ultimately contributing to a more sustainable future by providing practical insights for leaders, managers, and policymakers.This book should be a mandatory desktop reference for corporate directors, officers, advisors, legal counsel, accountants, and auditors who are engaged in sustainability factors of planning, performance, risk, reporting, and assurance. It also provides business leaders, academics, and students with a comprehensive understanding of how AI can be strategically integrated into business operations to enhance sustainability, drive innovation, and create long-term value.
Keywords: Artificial intelligence -- Business applications.; Sustainable development reporting.; Social accounting.; Environmental auditing.; elektronické knihy; electronic books